Odessa sea - Cussler, Clive; Cussler, Dirk (Cussler, Clive. Dirk Pitt adventure, 2017)
"Over the years, Dirk Pitt has always had a knack for finding trouble. This time, it has found him. Pitt, the director of the National Underwater and Marine Agency, is on the Black Sea, helping to locate a lost Ottoman shipwreck, when he responds to an urgent Mayday - "Under attack!" - from a nearby freighter. But when he and his colleague Al Giordino arrive, there is nobody there. Just dead bodies, a smell of sulfur in the air, and, as Pitt and Giordino explore, a blast from the stern that scuttles the ship swiftly, almost taking them with it. The more the two of them search for the secret of the death ship, the deeper they descend into an extraordinary series of discoveries. A desperate attempt in 1917 to preserve the wealth and power of the Romanov Empire. A Cold War bomber lost with a deadly cargo. A brilliant developer of advanced drone technology on an unknown mission.Modern-day nuclear smugglers, determined Ukrainian rebels, a beautiful anti-terrorism agent from Europol - all will combine to present Pitt with the most dangerous challenge of his career. And not only Pitt. His two children, marine engineer Dirk and oceanographer Summer, are exploring a mysterious shipwreck of their own, when they are catapulted into his orbit. The three of them are used to perilous situations - but this time, they may have found their match."--